Identification of Anti-tuberculosis Compounds From Aurone Analogs - Yang, Dong; Taylor, Zachary E.; Handy, Scott; Li, Shaoji; Liu, Jiawang; Stabenow, Jennifer; Zalduondo, Lillian; Jonsson, Colleen B.; Altman, Elliot; Kong, Ying (Frontiers in Microbiology, 2020)
The emergence of multidrug-resistant Mycobacterium tuberculosis (Mtb) strains has made tuberculosis (TB) control more difficult. Aurone derivatives have demonstrated promising anti-bacterial activities, but their effects against Mtb have not been thoroughly determined. In this study, we aimed to develop anti-TB compounds from aurone analogs. We used a fluorescent protein tdTomato labeled Mtb CDC1551 strain to screen 146 synthesized aurone derivatives for effective anti-TB compounds. The 9504, 9505, 9501, 9510, AA2A and AA8 aurones inhibited the growth of Mtb with minimal inhibitory concentrations of 6.25, 12.5, 25, 25, 25, and 50 µM, respectively. We also examined cytotoxicities of the six leads against the human liver cell line HepG2, the primate kidney cell line Vero and human monocyte THP-1 derived macrophages. Three of the aurone leads (9504, 9501, and 9510) showed low cytotoxic effects on all three cell lines and high Mtb inhibitory efficacy (selectivity index>10). Aurone 9504, 9501, AA2A, or AA8 significantly reduced the Mtb load in the lungs of infected mice after a 12-day treatment. We determined that the aurone leads inhibit Mtb chorismate synthase, an essential enzyme for aromatic acid synthesis. Our studies demonstrate the promise of synthetic aurones as novel anti-TB therapeutics.